Z „pomiędzy” Heaneya – Jarniewicz - Okulska, Inez (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The subject for the critical and literary comments in the present article is, in the first instance, the collection of essays devoted to the literary output of the Irish Nobel prize-winner Seamus Heaney written by Jerzy Jarniewicz and entitled “Wiersze pod dotyk”. Though this is the chief reason, but not the only one, as this seemingly innocent monograph book turns out to be a gem in itself with regard to the poetical artistry of the Polish author of the essays. And so, the reader finds the following: poetical language of description, poetical sensitivity in reading and a particular poetical manifesto that has a programme-character for Jarniewicz-poet. And all this is revealed form the eponymous “in between”, from between the verses, reading material, fascination and connotations of the author.